IMPLEMENTASI MODEL PEMBELAJARAN GEO-STAR UNTUK MENINGKATAN KEMAMPUAN BERPIKIR SPASIAL SISWA PADA MATERI HIDROLOGI FASE E KELAS X DI SMA NEGERI 2 BATANG ANAI - Julianti, Fadia; Suasti, Yurni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the implementation of the Geo-STAR model in improving the spatial thinking skills of tenth grade students at SMA Negeri 2 Batang Anai. This study is a quantitative study using a quasi-experimental method with a non-equivalent control group design. The population of this study was grade X consisting of seven classes, the sample was taken purposively where the learning schedule in both classes was carried out in the morning, namely for class X E.5 as the experimental class and class X E.6 as the control class. Data collection instruments included multiple-choice spatial thinking ability tests and essays, covering primitive spatial, simple spatial, and complex spatial. Statistical data analysis was carried out using the paired sample t-Test, independent sample t-Test and normalized gain (N-Gain) test. The results showed that the implementation of the Geo-STAR model had a significant effect on students' spatial thinking skills (p = 0.000 <0.05), with the average student score increasing from 69.69 (pretest) to 80.05 (posttest). In conclusion, the Geo-STAR model has a positive effect in stimulating students' spatial thinking skills, but requires a more flexible implementation timeframe to achieve optimal acceleration.